Teaching reading through cornell notes strategy - Susnifa Atun Sholikhah; S Sumani; Brigitta Septarini Rahmasari (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
The purposes of the research are to describe the implementation, advantages and disadvantages, and solution from disadvantages of teaching reading by using Cornell Note strategy. The research uses descriptive qualitative research as approach and type of research. The sources of data are social situation, participant, and document. The techniques of collecting data are observation, interview, and documentation. To know the validity of the data, the researcher uses methodology triangulation. The technique of data analysis are data condensation, data display, conclusion and verification.The result of the research shows that the implementation of Cornell Note strategy has three steps included pre-activity, whilst- activity, and post- activity. The pre-activities include greeting, praying, checking students’ attendence and explaining the purpose of the meeting. The whilst- activities, the teacher explains how the procedures to read the text by using Cornell Note strategy. The procedures are prepare the worksheet, takes note in right column, write the question in left column, summarize information in bottom space, recite the note. Lastly, post- activities include reviewing and making resume of the material. The advantages are; first, can help the students to analyze the important information in the text. Second, motivate to read a text. Third, train the students’ concentration. Lastly, make the students enjoy in learning reading. Meanwhile, the disadvantages are; first, the students are difficult to know the meaning of the word in the text and make the question with correct structure into English. Besides, the solutions for the disadvantages of implementation Cornell Note strategy are; first, the teacher gives axamples the students to make a simple question. Second, the students can search a difficult word in the dictionary. In this research, the researcher also gives suggestions for the teacher, students, the school and the onther researchers.